PENGEMBANGAN MEDIA STORY BOOK BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA TEMA 3 SUBTEMA 2 KELAS III SD - Rodiah, Siti; Nurmayani, Nurmayani; Tarigan, Daitin; Prawijaya, Septian; Ananda, Lala Jelita (Jurnal Merah Putih Sekolah Dasar, 2023)
This study aims to develop and produce appropriate, practical, and effective storybook learning media. The type of research used is Research and Development with the 4D model. The subjects in this study are subject matter experts, media experts, teachers, and 18 third-grade students at SDN 101776 Sampali. The object of this study is storybook media. The instruments used to collect data were observation questionnaires, teacher interviews, material and media validation questionnaires, media practicality questionnaires by education practitioners, student response questionnaires, and multiple-choice tests. The results of this study show that: (1) the feasibility of the story book learning media product based on the assessment of subject matter and media experts obtained an average percentage of 88.33% and 92.5% in the very feasible category. (2) The practicality of the learning media based on the results of teacher assessments was 91.6%, which is classified as very practical, and the practicality score based on student responses was 90.12%, which is also classified as very practical. (3) The effectiveness of the learning media was obtained from the results of the students' pre-test and post-test scores. The pre-test scores showed that only 48.61% of the students were in the “ineffective” category, while the post-test scores showed an increase to 85.27% in the “effective” category. Based on this, it can be concluded that the story book learning media based on contextual teaching and learning (CTL) is feasible, practical, and effective for use in the learning process in schools.